Deeper than Belief: Intuitive Judgment as a Context-Driven Process - Lang, Jacob; Körner, Christin; Körner, Annett (2023)
Based on “laws” of contagion and similarity, it is understood that people tend to believe that meanings associated with one object may be transferred onto another, and the meanings of the first may “contaminate” the second. The perceived contamination may influence the individual’s way of interacting with the object. We aimed to produce a rich description of individual differences that predict intuitive judgments in response to scenarios involving activation of contagion heuristics. Adolescents and adults in Germany completed a survey and provided rated responses to hypothetical scenarios. They also gave open-ended remarks on one scenario: whether they would wear a sweater that had belonged to Adolf Hitler if they were cold. Content analysis produced a composite description of reflections with insights into historical consciousness in contemporary Germany. Also examined was the extent to which quantitative responses were related to demographics, personality characteristics, supernatural beliefs, and responses to other scenarios.
Keywords: Superstition; Personality; Magical thinking; Historical Consciousness; contagion heuristics